PERTARUNGAN RELIGIUSITAS DI EROPA DALAM DUA NOVEL DAN BROWN - Nurhadi Nurhadi (LPMPP Universitas Negeri Yogyakarta, 2009)
AbstractIn his two novels, Angels Demons and The Da Vinci Code, Dan Browndescribes the clash of the Illuminati Order and Priory of Sion against the VaticanChurch. These secret societal groups are described as secret groups having thecommon roots and both are presented in the two novels although they are not themain theme. However, these two secret groups have the common relation to thestarting point of the development of religions in Europe. These groups are theagents of the emergence of residual paganism through Kabbalah and Old Egyptoccultism in Europe recently. They are known as Freemason, their ideology focuseson materialism and secular humanism, and atheism becomes their important faith.Although only fictional works, Browns two novels have taken part in thecontestation of religiosity struggle in Europe as a discourse.Keywords: religiosity struggle, Vatican Church, paganism, atheism